Whole genome analysis of Shigella sp. JZ001: a novel strain isolated from diarrheic suckling mice - Li, Xiang yu; Yang, Piao Piao; Tang, Yunzhu; Li, XiaoFeng; Jia, Xuejiao; Liu, Mengqi; Li, Yonggang; Zhao, Wei (Frontiers in Veterinary Science, 2025)
BackgroundShigella spp. are Gram-negative enteropathogens responsible for bacillary dysentery (shigellosis) in humans and animals. While the primary reservoirs of Shigella are historically recognized as humans and non-human primates, emerging evidence indicates an expanding host range encompassing diverse animal species. This study systematically characterizes a Shigella sp. strain isolated from diarrheic suckling mice.MethodsDiarrheic suckling mice intestinal contents were collected and analyzed using 16S rRNA sequencing technology. Shigella sp. JZ001 strain was isolated, purified, and identified. Bacterial morphology was examined by transmission electron microscopy. Carbon source utilization profiles were determined using BIOLOG GENIII MicroPlates™. Short-chain fatty acid (SCFA) composition was quantified by gas chromatography–mass spectrometry (GC–MS) following methyl-tert-butyl ether extraction. Polar lipid analysis was performed through two-dimensional thin-layer chromatography with detection using 10% ethanolic molybdatophosphoric acid. Whole genome sequencing was performed using a hybrid approach combining Illumina NovaSeq and Nanopore MinION platforms. Phylogenetic reconstruction was performed using maximum-likelihood algorithms implemented in MEGA.ResultsRotavirus-SA11 infected suckling mice exhibited watery feces 4 days post-infection. Intestinal contents were analyzed using 16S rRNA sequencing technology, which revealed a significant increase in the genus Shigella in the RV-infected group. A Shigella strain was isolated and purified from the intestinal contents and designated as JZ001. Polyphasic characterization confirmed that strain JZ001 belongs to the Enterobacteriaceae family and is phylogenetically closest to Shigella spp. The genome consists of a single circular chromosome (5,329,126 bp; G + C content 50.65%) and one plasmid (1,09829 bp, G + C content 40.14%). Comparative genomic analysis identified 24 Salmonella pathogenicity island (SPI)-like regions. Substrate assimilation tests demonstrated metabolic versatility, including utilization of D-Maltose, D-Trehalose, α-D-Glucose, D-Mannose, D-Fructose, D-Galactose and Propionic Acid. Cellular fatty acid methyl ester (FAME) analysis identified predominant components as: Dodecanoic acid (12:0; 11.08%), Tetradecanoic acid (14:0; 12.00%), Hexadecanoic acid (16:0; 21.55%), cycloheptadecanoic acid (17:0 cyclo; 13.99%), Dodecanal (12:0 aldehyde; 22.32%). The polar lipid profile consisted of diphosphatidylglycerol, phosphatidylglycerol, and phosphatidylethanolamine, with notable absence of aminolipids and aminophospholipids.ConclusionFirst study of murine Shigella JZ001 offers insights into genomic plasticity and host adaptation mechanisms. The genomic dataset lays foundation for host-pathogen studies and facilitates developing murine models for therapy evaluation.